To the Issue of Studying Ecological Emotional Experiences - Baranov, Vladyslav (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2023)
The article provides a theoretical analysis of research on environmental experiences in foreign and domestic psychology, focusing on the importance of environmental experiences for psychological health and psychological well-being. Approaches to the definition of environmental emotions and environmental anxiety are considered. Based on the synthesis of the analyzed literature, the author's definition of the concept of ecological experiences is proposed. Prospects for further research on the specified topic are determined.